SarkoLife: quality of life in patients undergoing multimodal soft tissue sarcoma treatment - Sebastian Hoffmann; Tabea Hoffmann; Vlatko Potkrajcic; Christoph K. W. Deinzer; Katrin Benzler; Lars Zender; Adrien Daigeler; Johannes Tobias Thiel (World Journal of Surgical Oncology)
Abstract Objective To assess the tolerability of multimodal therapy in soft tissue sarcoma patients, particularly with regard to their quality of life and level of distress. Materials and methods A retrospective cohort study enrolled individuals receiving sarcoma therapy at the sarcoma center of the University of Tuebingen between 2017 and 2022. Participants completed an online survey that included the EORTC’s questionnaire (QLQ-C30), coupled with the distress thermometer and demographic inquiries. The primary emphasis was on comparing three distinct modalities: Radiation, Chemotherapy and Surgery. The data were analysed performing one-way ANOVA. Results A total of 237 patients were included in the study. There was a significant difference (p < 0.001) in quality of life according to the EORTC scores (high score = high quality of life) between the different treatments: chemotherapy (mean: 26.8 [standard deviation: 19.5]), radiotherapy (51.0 [21.5]), and surgery (46.9 [28.3]). Similarly, a statistically significant discrepancy (p < 0.001) was found in average distress levels (high score = high level of distress) corresponding to each treatment type: radiation (5.0 [2.7]), surgery (6.0 [2.9]), and chemotherapy (7.4 [2.4]). The rates of patients willing to undergo the same treatment varied across groups, with the highest percentage observed in the surgery group (94.2%), followed by radiation (87.4%), and chemotherapy (73.5%). Conclusion Patients receiving multimodal therapy for soft tissue often find chemotherapy particularly demanding. Impairment of both quality of life and physical well-being is more likely and tends to be more severe compared with radiation or surgery. These observations should be taken into consideration when consenting patients and offering treatment plans.